Tindak Pidana Pencabulan Anak di bawah Umur oleh Aparat Penegak Hukum (Studi Putusan Nomor 71/PID.SUS/2013/PN.YK) - Agus Muzaqi (UIN Sunan Kalijaga Yogyakarta, 2014)
The children are one of precious assets of each nation. As a part of the futuregeneration, the children has the strategic role to determine the success of such a nation.The criminal action of decent toward the under age children becomes the acute symptomand its occurrence quantity increases higher in the society. Therefore, it draws thesociety’s awareness about the importance to overcome the criminal action of decent. Onthe other hand, Police Unit of Republic Indonesia (Polri), as one of country agent tomaintain the safety, orderliness, and service for the society has an importance role toprotect the children from this criminal action of indecent. However, it is very ironic thatthe fact shows the opposite where there is such a part of the police who becomes thesubject of this criminal indecent case toward the under age child such as the writer hasfound in the verdict of the Judge Council (MK) of the District Court YogyakartaNumber 71/PID.SUS/2013/PN.YK. From this case, the writer is very interestedto analyze that verdict in order to know the Judge Council’s consideration in giving theverdict for the police as the subject of the indecent criminal toward the under age childwhich is observed based on Undang-Undang Perlindungan Anak and KUHP.